‘You have one identity’: performing the self on Facebook and LinkedIn - van Dijck, José (Media, culture & society, 2013)
Social media are popular stages for self-expression, communication and self-promotion. Rather than facilitating online identity formation, they are sites of struggle between users, employers and platform owners to control online identities – a struggle played out at the level of the interface. This article offers a comparative interface analysis between Facebook and LinkedIn. While Facebook is particularly focused on facilitating personal self-presentation, LinkedIn’s interface caters towards the need for professional self-promotion. And yet, both platforms deploy similar principles of connectivity and narrative – strategies that can be succinctly revealed in recent interface changes. These changing digital architectures form the necessary backdrop for asking critical questions about online self-presentation: How are public identities shaped through platform interfaces? How do these features enable and constrain the sculpting of personal and professional persona? And what are the consequences of imposed connectivity and narrative uniformity on people’s online identities?